Palliative care follow-up for cancer patients combining day-hospital visits and telemedicine: What feasibility? - Valerie Mauries-Saffon; Alfonsina Faya-Robles; Marie Bourgouin; Sebastien Lamy; Nathalie Caunes-Hilary; Bettina Couderc (PLoS ONE, 2026)
Background Due to the increasing life expectancy of patients with cancer, palliative care services are increasingly solicited to provide follow-up for individuals living at home. The implementation of teleconsultations represents a potential solution to extend access to palliative care follow-up to a larger number of patients. The aim of this study is to demonstrate the a priori acceptance of teleconsultations among all patients admitted to palliative care, as well as the feasibility of their implementation. We therefore initially explored whether a specific patient profile might limit acceptance or feasibility of teleconsultations (e.g., older patients, patients unfamiliar with digital technologies, gender differences, social status, economic status, or place of residence), and we identified patients’ expectations and concerns regarding teleconsultation. The secondary objective is to describe the contribution of monthly remote consultations (telemedicine), conducted in parallel with quarterly day-hospital follow-up by a palliative care team, for patients with cancer, in anticipating potential deterioration in their overall clinical condition. Methods We included 36 patients at the time of their first admission to the palliative care day hospital. Upon enrollment, participants completed a questionnaire on demographic characteristics as well as their expectations and/or reluctance regarding teleconsultations. Patients were scheduled to receive monthly teleconsultations (at 1 and 2 months), followed by an in-person visit at 3 months. Results With regard to feasibility and acceptability, our findings indicate that age, sex, socioeconomic status, or underlying disease did not influence patient adherence or the successful conduct of teleconsultations. Patients expressed few negative preconceptions regarding their inclusion in the study. Concerning the clinical contribution of monthly consultations, interviewed patients reported a perceived benefit of monthly teleconsultations for both their psychological support and clinical management, and expressed a desire to continue monthly follow-up by teleconsultation beyond the three-month study period. Conclusions In the absence of the possibility of monthly in-person consultations, we highlight the relevance of developing teleconsultations for patients receiving palliative oncological care, regardless of their profile.